2017
DOI: 10.1007/s12602-017-9339-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Vaginal Lactobacillus Supernatants on Cervical Cancer Cells

Abstract: Lactobacilli have been shown to inhibit the proliferation of several types of cancer cells, but the effects of vaginal Lactobacilli on cervical cancer cells have seldom been reported. We incubated Caski cells with supernatants of predominant strains in the vagina and investigated their effects on cell growth and the possible mechanisms. Cell-free supernatants of Lactobacillus crispatus, L. jensenii, and L. gasseri were prepared and purified. Caski cells were treated with various concentrations of Lactobacillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…The results of this study show that L. crispatus protects the cervical epithelial barrier in the presence of an inflammatory stimulus; however, the mechanisms regulating this interaction will need further investigation as these experiments are not able to identify if L. crispatus bacteria-free supernatants have the ability to block LPS binding to the TLR4 receptor or activate the host immune response to prevent the inflammatory insult. While there are previous studies that have shown a protective effect of L. crispatus in the face of Prevotella bivia and G. vaginalis (BV-associated bacteria) ( Atassi et al, 2006 ), E. coli ( Ghartey et al, 2014 ), HIV acquisition ( Gosmann et al, 2017 ), and cervical cancer (human papillomavirus oncogenes) ( Wang et al, 2017 ), none have investigated the direct protective effects of L. crispatus on either the cervical epithelial barrier or the biological mechanisms involved in this effect. In the presence of L. crispatus bacteria-free supernatants, the G. vaginalis -induced increase in miRNA expression was robustly reduced, suggesting that L. crispatus bacteria-free supernatants are able to mitigate the G. vaginalis -mediated disruption of the cervical epithelial barrier through a reduction in miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study show that L. crispatus protects the cervical epithelial barrier in the presence of an inflammatory stimulus; however, the mechanisms regulating this interaction will need further investigation as these experiments are not able to identify if L. crispatus bacteria-free supernatants have the ability to block LPS binding to the TLR4 receptor or activate the host immune response to prevent the inflammatory insult. While there are previous studies that have shown a protective effect of L. crispatus in the face of Prevotella bivia and G. vaginalis (BV-associated bacteria) ( Atassi et al, 2006 ), E. coli ( Ghartey et al, 2014 ), HIV acquisition ( Gosmann et al, 2017 ), and cervical cancer (human papillomavirus oncogenes) ( Wang et al, 2017 ), none have investigated the direct protective effects of L. crispatus on either the cervical epithelial barrier or the biological mechanisms involved in this effect. In the presence of L. crispatus bacteria-free supernatants, the G. vaginalis -induced increase in miRNA expression was robustly reduced, suggesting that L. crispatus bacteria-free supernatants are able to mitigate the G. vaginalis -mediated disruption of the cervical epithelial barrier through a reduction in miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in-vitro studies suggested that vaginal microbiota may increase the apoptosis of cancer cells or may provoke the anti-inflammatory cells like dendritic, Treg and cytokines. [66][67][68][69] The lack of efficient treatment to counter antibiotic resistance to bacterial infections and the intravaginal application of lactobacilli and lactoferrin may be the narrative and capable therapeutic approach to reinstate the mucosal immune homeostasis. 25…”
Section: Probiotic Therapymentioning
confidence: 99%
“…Lactobacillus spp. is able to outcompete growth of Gardnerella and Prevotella species [48] and has been shown to inhibit growth of cervical cancer cell lines [49]. Further in vitro studies have demonstrated that L. crispatus in particular is protective against in ammationmediated increases in ectocervical cell permeability, as the endocervical production of IL-6 and IL-8 signi cantly decreased after exposure to L. crispatus bacteria-free supernatants [50].…”
Section: Discussionmentioning
confidence: 99%